PERAN BIDAN TERHADAP PEMAHAMAN IBU HAMIL TENTANG ASI EKSKLUSIF DI DESA TANJUNG MORAWA B DELI SERDANG - Friska Sitorus; Dewi R Bancin; Surya Anita (Jurnal Reproductive Health, 2021)
The understanding of pregnant women about exclusive breastfeeding as evidenced by Exclusive breastfeeding is breastfeeding from birth until the child is 6 months old. During this period children are not expected to get additional fluids, such as formula milk, lemon juice, tea water, honey, and plain water. In exclusive breastfeeding, children are also not given additional food such as bananas, biscuits, rice porridge, teams, and so on. Exclusive breastfeeding for up to 6 months can meet the needs of children, and requires additional food at the age of over 6 months (Maryunani, 2012). The role of midwives in promoting exclusive breastfeeding can be started from the time the mother is pregnant. When pregnant women check their pregnancies, pregnant women will get information about the benefits of breastfeeding and how to successfully breastfeed when their babies are born (Atik, 2016). The role of a good midwife will increase a good understanding for pregnant women about exclusive breastfeeding 37.9%, and there is an influence between the role of midwives and the value of PV value 0.003. Pregnant women make antenatal care visits at least 4 times during pregnancy to the midwife or to the nearest health facility so that they get clear information about exclusive breastfeeding. For health workers to be more intensive in conducting home visits to check on mothers' pregnancies as well as providing counseling on exclusive breastfeeding.